Fish, Including Their Carcasses, Are Net Nutrient Sources to the Water Column of a Eutrophic Lake - Nobre, Regina L. G.; Carneiro, Luciana S.; Panek, Sarah E.; González, Maria J.; Vanni, Michael J. (Frontiers in Ecology and Evolution, 2019)
Animals can act as sources or sinks of nutrients in ecosystems, and their role in this context may depend on the fate of nutrients in decomposing carcasses, which may contain recalcitrant structures such as bones. Our goal was to assess whether a fish population with high biomass is a source or sink of nutrients to the pelagic zone of a eutrophic lake over time scales ranging from days to 20 years. We developed a population-level model based on a 20-year (1996 - 2015) dataset for gizzard shad (Dorosoma cepedianum) in Acton Lake, a eutrophic reservoir in southwest Ohio, U.S.A. In addition, we used data from experiments that quantified nutrient mineralization rates from carcasses as functions of fish size and temperature. Nitrogen (N) and phosphorus (P) remineralization rates from carcasses increased with temperature and decreased with fish size. Over the 20 years, almost all (~99%) of the nitrogen (N) and phosphorus (P) produced as gizzard shad carcasses was remineralized back to the water column. At the ecosystem scale, carcass nutrient dynamics followed a seasonal pattern, with a net accumulation of carcass nutrients in winter but a net depletion of the carcass nutrient pool in summer, due to mineralization. Dynamics of carcass production and remineralization were strongly influenced by young-of-year fish (YOY), for both N and P, because the number of fish born varied considerably across years, YOY have high mortality rates, and YOY carcasses decompose rapidly. On an annual basis, in a few years, biomass production was higher than mineralization, suggesting that in these years fish biomass may act as a nutrient sink at the annual scale. However, nutrient excretion by the population greatly exceeded sequestration of nutrients in biomass (living and dead). Because most of the nutrients consumed (and excreted) by this population are derived from the benthos, at the lake-wide scale and considering all fluxes, the population is a significant net source of nutrients to the pelagic habitat. Our model demonstrates the relevance of considering spatial and temporal scale as well as long-term population dynamics when studying the role of animals as nutrient sources or sinks.